Space as a warfighting domain: Reshaping policy to execute 21st century spacepower. Issue 4 (25th July 2022) - Lambakis, Steve
Abstract: There has been a shift in opinion in the U.S. governing and defense-planning circles causing leaders to accept the reality that space is a warfighting domain. Despite arguments put forth over the past several decades by sanctuary-policy proponents that space should remain free of Earth's conflicts, reality has dictated otherwise as other powerful nations have acquired the capabilities to execute offensive and defensive operations within the space domain. The U.S. national vision for space must fold in the reality of possible combat engagements in space. If we are to ensure space dominance, the U.S. administration and the nation's lawmakers will have to take some policy risks in a time when near-peer competition in space is growing rapidly and significantly. Inaction, inadequate action, or misguided action will have negative effects, and place at risk the U.S. ability to enforce its deterrence strategy and fight a battle that may involve space warfare.